2021
DOI: 10.3390/su13116501
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Conceptual Development of Industry 4.0, Servitisation, and Circular Economy: A Systematic Literature Review

Abstract: Industry 4.0 (I4.0) technologies have been highlighted in recent literature as enablers of servitisation. Simultaneously, businesses are advised to implement a circular economy (CE) to bring new opportunities. However, it is pertinent to mention that little attention has been given to assess the role of I4.0 in adopting the CE and servitisation in a fully integrated manner. This research fills this gap by developing a conceptual framework through a systematic literature review of 139 studies investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 166 publications
(469 reference statements)
0
53
0
1
Order By: Relevance
“…Simultaneously, businesses are advised to implement a circular economy (CE) to bring new opportunities. Atif et al find that the use of Industry 4.0 technologies in a service-oriented business model is beneficial for companies to create value [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simultaneously, businesses are advised to implement a circular economy (CE) to bring new opportunities. Atif et al find that the use of Industry 4.0 technologies in a service-oriented business model is beneficial for companies to create value [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Impact on jobs and knowledge management due to application of IoT in the manufacturing Industry 4.0 [16,36,41,118,125] With machines taking up most of the tasks in a smart factory, employees will take on more complex roles in these factories. This will need special skills and knowledge to fill these job roles, creating a vast skill gap with retiring experienced and skilled workers.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…The high costs of implementing IoT technologies add to the burden for manufacturers, thus leading to slow adoption of these technologies in some sectors [14,69]. The empirical research also reported costs such as workforce training and development, systems integrations, security and opportunity costs of the learning curve [118,119].…”
mentioning
confidence: 99%
“…Leach [2] conducted a comprehensive review of available sources, and it shows the richness of the literature available. There are also numerous articles that focus on comprehensive review of specific theme, such as sustainability in healthcare [3], circular economy [4], or gender sustainability in corporate boards [5], which provide a wide range of sources, showing that sustainability is a popular subject of scientific enquiry. Diverse social groups may have different and possibly opposing interests, priorities, and perspectives, which makes the matter highly politicized and an object of continual negotiation and renegotiation.…”
Section: Introductionmentioning
confidence: 99%